Optimizing LZW text compression algorithm via multithreading programming - Tan, C.E; Tan, L.S; Lau, S.P (IEEE, 2009)
Due to the emerging multimedia technology, multimedia files such as text, image, audio and video files are widely used. These multimedia files take hundreds time more space as compared to early day's media files. Thus, demand for efficient compression algorithm is in great needs. Currently, a lot of general purpose multi-core processor machines and systems are widely available. However, many compression algorithms have not been taking advantage of being optimized for these processors. This paper explores the multithreaded compression algorithm to take advantages offered by multi-core processor